INDICATORS FOR ASSESSING THE NEED FOR HIGHLY QUALIFIED SPECIALISTS (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article develops criteria for assessing the need for highly qualified specialists. The need for skilled migrants is identified by industry. Several methods of analysis based on country demographic data were used. The main sponsors and most in-demand areas of the US H-1B visa were studied. An analysis of the educational level of candidates accepted to Canada is presented.
Keywords: Highly skilled migrant, net migration, education level.